POLA KOMUNIKASI KELUARGA SINGLE PARENT DALAM MENGEMBANGKAN KONSEP DIRI ANAK PEREMPUAN DI KECAMATAN WAJO KOTA MAKASSAR - Nurul Aulia , Ihsanie; Muttaqin Mustari , Andi; Idris, Muhammad (RESPON JURNAL ILMIAH MAHASISWA ILMU KOMUNIKASI, 2022)
The purpose of this study was to determine the pattern of family communication in the development of the self-concept of girls (single parent) in Wajo District, Makassar City and to determine the pattern of development (Single Parent) in developing the self-concept of girls with their families in order to establish good communication. This research uses descriptive analysis qualitative research method. This study intends to describe the description of single parents in developing their daughter's self-concept through family communication patterns to guide and provide support to daughters. The selected informants include people who are selected on the basis of certain criteria. This research was conducted by collecting data through observation, interviews, and documentation. This research was conducted for one month and located in Wajo District, Makassar City. The results of this study indicate that the pattern of family communication in developing the self- concept of single mother girls by using communication patterns is given through interpersonal communication where parents are communicators and the efforts given by single parents to girls are generated from experiences that have been passed and communication with parents make the nature, behavior, emotional, and social can be positive or negative. The form of communication used by single mothers in developing their daughter's self- concept uses interpersonal communication in the form of direction, teachings, guidance, experience and word of mouth motivation. The guidance provided is maximal enough to develop the child's self-concept as a guide in the future.